Synthesis Of Ordered Mesoporous Sno2 Using Sba-15 Nanocasting Template And Its Performance As A Gas Sensor For Hydrogen Sulfide - Ramasamy, Ram Ghautaam P. (Universiti Sains Malaysia, 2022)
The synthesis parameters of ordered mesoporous SBA-15 silica, ordered mesoporous SnO2 replicas and the replicas performance as a gas sensor towards hydrogen sulfide gas has been investigated. Ordered mesoporous SBA-15 silica was first synthesised to produce a hard template for the nanocasting of SnO2. Ordered mesoporous silica was then produced using the SBA-15 hard template via nanocasting under different cycles of infiltration and different methods of infiltration. The validity of the mesostructure of the synthesised SBA-15 silica and ordered mesoporous SnO2 replicas were proven by characterization methods involving XRD analysis, BET analysis and SEM analysis. The sensitivity of the different types of SnO2 replicas were then simulated using MATLAB. The code was derived from the mathematical modelling of gas diffusion extracted from a specific literature and further modified by referring to other pieces of literature. The effect of pore sizes on the sensitivity of SnO2 replicas towards hydrogen sulfide gas were investigated by using the pore radius data presented in the BET analysis. The effect of operating temperatures in different gas concentrations of hydrogen sulfide on the gas sensitivity of SnO2 replicas were also investigated. The simulated results show that a larger pore radius corresponds to a higher gas sensitivity whereas the optimum performance of the SnO2 gas sensor in different gas concentrations are attributed to a temperature of 313 K.